A garlanded portrait of Jesus in the reception hall - Mumbai Archive Project (Jio Institute, 2024)
A garlanded portrait of Jesus greets visitors in the reception hall. The Latin phrase adveniat regnum tumm, written on the scroll above, translates as ‘May your kingdom come.’ This particular phrase is associated with Christ the King, referring to the idea of the Kingdom of God, where Christ is described as being seated at the right hand of God. In front of the portrait is a small figure of Mother Mary holding the infant Jesus.